Analysis of the feasibility of investing in consumer goods industry stocks using the capm approach for the period January 2005 - December 2007 - Niken Dwi Nastiti (Indonesia Auditing Research Journal, 2021)
The purpose of this research is to know wheter some stocks is worthy or not to be bought. The objective of this research is to find out the investment advisability of consumer goods industry stocks in Indonesia Stock Exchange. The object of this research is stock which listed in Indonesia Stock Exchange (BEI). The writer takes example of 30 stocks of consumer goods industry as the object of the research. The research’s period is from January 2005 up to December 2007. The method being used in this research is Capital Asset Pricing Model (CAPM). The result of the CAPM model, it is found that there are 20 undervalue stocks and 10 overvalue stocks in consumer goods industry in a research’s period.